Maîtresse - Schroeder, Barbet; Almendros, Néstor; Depardieu, Gérard; Ogier, Bulle; Rouyer, André (bfi, 2003)
A young provincial in search of adventure stumbles into the subterranean world of sadomasochism when he is implicated in the burglary of a Paris apartment. The apartment's mistress runs a two-floor operation, all respectability above and a dungeon of punishment-seeking clients below. After the young man becomes her upstairs lover, she finds that the two levels interfere with each other. Barbet Schroeder's Maitresse examines the line between fantasy and reality, decadence and deprivation, and the distance one will go for love. [dvdovernight.com]